Biology Learning Based ICT in Indonesia: A Systematic Literature Review - Khairil Hadi; Wawan Sudatha; Kadek Suartama; Made Hery Santosa (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to identify, analyze, and synthesize key findings regarding the implementation of technology-based biology learning in Indonesia. This study is a Systematic Literature Review (SLR) using the PRISMA model, which includes the stages of identification, screening, eligibility, and inclusion. The data search process utilized search engines and databases such as Google Search, Google Scholar, ResearchGate, SINTA, and Scopus, using keywords related to technology in Biology education. Inclusion criteria for article selection included publications from 2020–2025, experimental articles in English, indexed in SINTA (S1–S2) and Scopus (Q1–Q4), accessible, tested in Indonesia, written by authors from Biology education programs, and thematically relevant. Data analysis was conducted descriptively to identify trends in technology-based Biology learning and to highlight contributions and important information regarding the use of ICT in Biology education in Indonesia. The trend in scientific publications on ICT in Biology education shows positive development with a total of 11 publications between 2020–2025. However, most articles are still indexed in Scopus Q3 and Q4 journals, as well as Sinta 1 and 2. The absence of publications in Scopus Q1 and Q2 journals indicates the challenges faced by Indonesian researchers, such as high writing standards, strict review processes, and a lack of understanding of publication ethics and scientific writing techniques. The use of technology in biology education in Indonesia includes tools such as Lectora Inspire, audio, video, e-books, Zoom, Learning Management Systems (LMS), Digital Mind Maps (DMM), Augmented Reality (AR), Prezi, web-based resources, digital posters, and virtual labs (Gizmos).